Determinants of Success in Treatment of Tuberculosis (TB) Patients at the Karang Rejo Health Center, Balikpapan City - Aspiansyah Aspiansyah (Jurnal Indonesia Sosial Sains, 2023)
Tuberculosis is one of the infectious diseases that is still a public health problem around the world. Balikpapan City in 2020, the number of patients infected with tuberculosis was 937 patients. As for 2021, there are 1,152 new patients and for 2022 until June there are 566 new patients. According to data obtained by the Karang Rejo Health Center, it is known that the number of patients infected with tuberculosis in 2020 was 36 people, then in 2021 as many as 18 people, and in 2022 as many as 17 people. This study aims to determine the determining factors for the success of treatment of tuberculosis (TB) patients at the Karang Rejo Health Center, Balikpapan City. This study used the design method of cross-sectional analytical research. The sample in this study was 17 patients in 2022. Using data analysis through two steps, namely univariate analysis and bivariate analysis using the Chi Square test and the Fisher's Exact test. The results showed that there was no significant association between treatment status (P-Value 0.63), age (P-Value 0.46), sex (P-Value 0.56), occupation (P-Value 0.48), diagnosis type (P-Value 0.27), OAT guidance (P-Value 0.56) and adherence rate to cadres (P-Value 0.79) with successful tuberculosis treatment. Meanwhile, there is a relationship between the source of the drug and the success of tuberculosis treatment with a P-Value of 0.05